If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5n-33=9n-81
We move all terms to the left:
5n-33-(9n-81)=0
We get rid of parentheses
5n-9n+81-33=0
We add all the numbers together, and all the variables
-4n+48=0
We move all terms containing n to the left, all other terms to the right
-4n=-48
n=-48/-4
n=+12
| 2x+1=6x+30 | | 8(3n-9)-2n=9n-7 | | 2x-26=4x-61 | | 7x-3(x+1)=x-12 | | 7=z–9 | | 8x-15=2x+6 | | –6s=–s+5 | | 13-8m-12=61 | | 1/3+2/3(3s+1)=1–s+2/3 | | 4x+5=5(x-1)+x | | 8=-2(r+-5) | | 1/3(24p=66)=3p+43 | | 13+23(3s+1)=1–s+23 | | p÷-9=12 | | 78+.4x=82 | | 14/15=42/x | | -2(1-1x)-3(1x+1)=0 | | 82+.4x=78 | | 6=p-30 | | 6z-7=37 | | 12x-16=4(3x+8) | | 1/5(10-5x)=1/3(-3x+6) | | -30h=-150 | | 8+12p=18 | | f+59=85 | | –3+6f=9+8f | | 8x+5+9x-8=180 | | -5x=-8.4 | | 4f=-412 | | 5z-(2z-23)=20z+22-2z | | x/2+4=51 | | .-5x=-8.4 |